Combined high hydrostatic pressure and thermal treatments fully inactivate trypsin inhibitors and lipoxygenase and improve protein solubility and physical stability of calcium-added soymilk - Manassero, Carlos Alberto; Vaudagna, Sergio Ramon; Sancho, Ana Maria; Añón, María Cristina; Speroni, Francisco (2018)
The objective of this work was to assess the possibility of obtaining calcium-added soymilk with acceptable characteristics regarding protein solubility and physical stability, and inactivation of trypsin inhibitors and lipoxygenase, through a combined thermal-high hydrostatic pressure treatment. A Doehlert design was applied to study the effect of combining pressure levels (500–700 MPa), initial temperatures (45–65 °C) and CaCl2 concentrations (5–15 mmol L− 1). Results showed that protein solubility was a function of CaCl2 concentration (p < 0.005), and that inactivation of trypsin inhibitors was a function of pressure level and temperature (p < 0.005). Lipoxygenase activity was fully inactivated in most of the conditions tested. Physical stability was improved by the combined treatments: depending on calcium concentration, either no settling was detected in a 5-day period or a less conspicuous phase separation was observed. Our results indicate that some combined thermal-high hydrostatic pressure treatments allow the preparation of calcium-enriched soymilks with improved physical stability without additives such as chelating agents, and acceptable in terms of full inactivation of trypsin inhibitors and lipoxygenase. Industrial relevance: An analysis of the effect of the combination of high hydrostatic and thermal treatments on calcium-added soymilk is introduced in the present study. Some processing conditions were found to allow the obtention of a product with improved protein solubility and physical stability, and with inactivated trypsin inhibitors and lipoxygenase enzyme. This information could be beneficial considering the reduction of process time and energetic costs, because the assayed combination of thermal and high pressure treatments takes advantage of the instantaneous compression heating. Thus, the results provided in the present work could be useful to prepare an acceptable calcium-added soymilk.